2021
DOI: 10.3390/ijms22073511
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cerebellar Grey Matter Alterations in Bipolar and Cerebellar Patients: Evidence from Voxel-Based Analysis

Abstract: The aim of this study was to compare the patterns of cerebellar alterations associated with bipolar disease with those induced by the presence of cerebellar neurodegenerative pathologies to clarify the potential cerebellar contribution to bipolar affective disturbance. Twenty-nine patients affected by bipolar disorder, 32 subjects affected by cerebellar neurodegenerative pathologies, and 37 age-matched healthy subjects underwent a 3T MRI protocol. A voxel-based morphometry analysis was used to show similaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…Among the behavioral alterations most commonly reported in these patients, changes in the emotional sphere are described, such as greater irritability, impulsivity, anxiety, dysphoria, emotional lability, difficulty in recognizing emotions, and attributing mental states of others, components that fall into the SC domain (Schmahmann and Sherman, 1998 ; Lupo et al, 2018a , b ; Clausi et al, 2019b ). On the other hand, several clinical studies have highlighted the presence of structural alterations of the cerebellum in subjects affected by various psychopathologies, such as schizophrenia (Okugawa et al, 2007 ), major depressive disorder (Bora and Berk, 2016 ), and bipolar disorder (Sani et al, 2016 ; Lupo et al, 2021 ), leading to the hypothesis that the cerebellum may be involved in the genesis of some typical symptoms of these disorders. Different studies aimed at analyzing the anatomical substrate of BD have found a significant pattern of atrophy involving cerebellar regions, such as the cerebellar vermis, the anterior lobule V and posterior lobules Crus I and Crus II (Mills et al, 2005 ; Lupo et al, 2021 ), which are known to be strictly connected to frontal, temporal, and limbic social brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the behavioral alterations most commonly reported in these patients, changes in the emotional sphere are described, such as greater irritability, impulsivity, anxiety, dysphoria, emotional lability, difficulty in recognizing emotions, and attributing mental states of others, components that fall into the SC domain (Schmahmann and Sherman, 1998 ; Lupo et al, 2018a , b ; Clausi et al, 2019b ). On the other hand, several clinical studies have highlighted the presence of structural alterations of the cerebellum in subjects affected by various psychopathologies, such as schizophrenia (Okugawa et al, 2007 ), major depressive disorder (Bora and Berk, 2016 ), and bipolar disorder (Sani et al, 2016 ; Lupo et al, 2021 ), leading to the hypothesis that the cerebellum may be involved in the genesis of some typical symptoms of these disorders. Different studies aimed at analyzing the anatomical substrate of BD have found a significant pattern of atrophy involving cerebellar regions, such as the cerebellar vermis, the anterior lobule V and posterior lobules Crus I and Crus II (Mills et al, 2005 ; Lupo et al, 2021 ), which are known to be strictly connected to frontal, temporal, and limbic social brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the cerebellar cognitive-affective syndrome (CCAS) [ 9 ], cerebellar alterations have been related to mood disturbances following both pure cerebellar lesion and neurodegenerative cerebellar pathologies [ 14 , 39 ]. Cerebellar structural alterations have been extensively reported in BD [ 3 , 16 , 40 ]. From an anatomical point of view, this is supported by the close cerebellar connections with the prefrontal-striatal-circuits and limbic structures, i.e., the amygdala and the hippocampus [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the abnormal FC in BD patients has been consistently reported during acute mood episodes [18], a persistent FC vulnerability has been hypothesized also during euthymia when bipolar patients exhibit minimal symptoms by definition [19]. This is probably the result of over-reactive emotional brain networks (i.e., anterior limbic network) that would always leave patients at risk for mood and cognitive disturbances [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, we further suggest that the posterior cerebellum may play a central role in social dysfunctions observed in many clinical pathologies. Indeed, deficits in mentalizing at large, and in the posterior cerebellum in particular, may play a crucial role in the onset and maintenance of psychiatric disorders related to limited mentalizing and emotion recognition, such as autism spectrum disorder [12][13][14], depression [15,16], bipolar disorder [17], obsessive compulsive disorder [18][19][20][21], addiction [22][23][24][25], and schizophrenia [26][27][28][29][30].…”
Section: Goal and Outlinementioning
confidence: 99%